The genome of Corydalis reveals the evolution of benzylisoquinoline alkaloid biosynthesis in Ranunculales. (21st May 2022) - Xu, Zhichao; Li, Zhen; Ren, Fengming; Gao, Ranran; Wang, Zhe; Zhang, Jinlan; Zhao, Tao; Ma, Xiao; Pu, Xiangdong; Xin, Tianyi; Rombauts, Stephane; Sun, Wei; et al.
SUMMARY: Species belonging to the order Ranunculales have attracted much attention because of their phylogenetic position as a sister group to all other eudicot lineages and their ability to produce unique yet diverse benzylisoquinoline alkaloids (BIAs). The Papaveraceae family in Ranunculales is often used as a model system for studying BIA biosynthesis. Here, we report the chromosome‐level genome assembly of Corydalis tomentella, a species of Fumarioideae, one of the two subfamilies of Papaveraceae. Based on comparisons of sequenced Ranunculalean species, we present clear evidence of a shared whole‐genome duplication (WGD) event that has occurred before the divergence of Ranunculales but after its divergence from other eudicot lineages. The C. tomentella genome enabled us to integrate isotopic labeling and comparative genomics to reconstruct the BIA biosynthetic pathway for both sanguinarine biosynthesis shared by papaveraceous species and the cavidine biosynthesis that is specific to Corydalis . Also, our comparative analysis revealed that gene duplications, especially tandem gene duplications, underlie the diversification of BIA biosynthetic pathways in Ranunculales. In particular, tandemly duplicated berberine bridge enzyme‐like genes appear to be involved in cavidine biosynthesis. In conclusion, our study of the C. tomentella genome provides important insights into the occurrence of WGDs during the early evolution of eudicots, as well as into the evolution of BIA biosynthesis in Ranunculales. Significance Statement: Here, we report the chromosome‐level genome of Corydalis tomentella and present a shared whole‐genome duplication event of Ranunculales, differing from the paleohexaploidy event of core eudicots. The genome enabled us to reconstruct the BIA biosynthetic pathway for both sanguinarine biosynthesis shared by papaveraceous species and the cavidine biosynthesis that is specific to Corydalis .